2D and 3D QSAR Analysis of Imidazole Derivatives as Heme Oxygenase Inhibitor - Darshana Gohate; Parul Mehta (Current Research in Pharmaceutical Sciences, 2020)
Selective inhibition of heme oxygenase is an important strategy in design of potent inhibitors of enzyme for the treatment of neonatal jaundice, cancer and many more. QSAR analysis is employed for a given set of compounds containing imidazole pharmacophore in order to establish a relationship between the biological activity and related descriptors, which provides us an idea to gain a potent inhibitor with lesser side effects. In this paper we present results of 2D and 3D QSAR studies of series of 26 molecules containing imidazole pharmacophore as selective heme oxygenase inhibitor using V Life MDS 3.5 Software. The 2D QSAR studies was performed using Partial Least Square Regression method and the 3D QSAR studies was performed using k- Nearest Neighbor Molecular Field Analysis(kNN- MFA) method. The analysis has produced good predictive and statistically significant QSAR models. 2D QSAR studies produced good statistical model with r2 value 0.8487, cross validated r2 value 0.6553 and prd_r2 value 0.7478 by PLSR method while 3D QSAR model gave statistical value of cross validated r2 value 0.5493 and pred_r2 value 0.3358. The results of the QSAR analysis suggested that the 2-D descriptor viz. physicochemical and alignment independent played an important role for heme oxygenase inhibition and the 3-D descriptors electrostatic and steric revealed the relative positions and range for substitution in a molecule. In 3D model, grid suggested that a positive electrostatic potential is favorable for increase in biological activity and the steric field with negative range and the negative range indicates that negative steric potential is favorable for increase in the activity. Thus, the descriptors generated by 2-D and 3-D QSAR analysis were useful in designing of potent molecules.